If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(1 + 6r) = 14 + -1r (1 * -3 + 6r * -3) = 14 + -1r (-3 + -18r) = 14 + -1r Solving -3 + -18r = 14 + -1r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add 'r' to each side of the equation. -3 + -18r + r = 14 + -1r + r Combine like terms: -18r + r = -17r -3 + -17r = 14 + -1r + r Combine like terms: -1r + r = 0 -3 + -17r = 14 + 0 -3 + -17r = 14 Add '3' to each side of the equation. -3 + 3 + -17r = 14 + 3 Combine like terms: -3 + 3 = 0 0 + -17r = 14 + 3 -17r = 14 + 3 Combine like terms: 14 + 3 = 17 -17r = 17 Divide each side by '-17'. r = -1 Simplifying r = -1
| -4(x-4)+6=22 | | 12b-5c+5b+1= | | 16x+3y= | | 3[4+2(y-1)]=36 | | -4x+90=50 | | 7=5+2(7c+1) | | 4-12=5s+51 | | (50-2x)*x=200 | | (7+2)xX+1= | | 5x+61=73+2x | | -g=1.5g-3 | | m(x)=(3x-1)(3-x)+4x^3+19 | | y=(20+x)(3000-100x) | | -0.75x=0.86 | | (3-9x)= | | 3=4-3(5c-1) | | 20+10m=200 | | 5b-14-3b=30 | | 15-5x=26 | | 6x+7x=16 | | 2x-2=4(x-1) | | 9a+3a+12=36 | | -5+7(k+6)=93 | | 6(-p)=54 | | x^2+4x+2=5x+7 | | -2m+19= | | 35+80h=915 | | 73-17=46+7 | | -9(8-9m+n)= | | 3x^3-4x^3= | | -4(7v-7)+5v=-87 | | 2x^2-20x+100=108 |